2014
DOI: 10.4038/engineer.v47i2.6865
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite Removal from Drinking Water using Naturally available Laterite in Sri Lanka

Abstract: Abstract:Arsenite, As(III) is the most soluble form of arsenic species. Arsenic removal efficiency by laterite (commonly found in Sri Lanka) was examined as a function of pH, initial arsenite concentration, laterite dosage, contact time and mixing rate. More than 90% arsenite removal could be achieved within 5 minutes when pH is around 10. By treating the water at this pH range, the current USEPA standard for arsenic in drinking water (10 ppb) can be maintained when the arsenite / laterite ratio is less than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…19 In Sri Lanka naturally obtainable laterite was used as an effective adsorbent for removing arsenic from contaminated water. 21 The dominant form of arsenic in water is arsenate which can also be removed by using laterite as adsorption material. 22 In a study, operational conditions were accessed for evaluating the natural efficiency of laterite to remove As(V) from groundwater after determining the adsorption capacity through the Langmuir isotherm model, which was 0.565 mg g -1 .…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In Sri Lanka naturally obtainable laterite was used as an effective adsorbent for removing arsenic from contaminated water. 21 The dominant form of arsenic in water is arsenate which can also be removed by using laterite as adsorption material. 22 In a study, operational conditions were accessed for evaluating the natural efficiency of laterite to remove As(V) from groundwater after determining the adsorption capacity through the Langmuir isotherm model, which was 0.565 mg g -1 .…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…Role of pH in arsenic removal efficiency of laterite was studied and showed that at pH 10 more than 90 % arsenite removed and less than 10 µg L -1 concentration can be maintained within 5 minutes by keeping arsenite and laterite ratio less than 10 (mg g -1 ). 21 Electrical conductivity indicates the amount of dissolved ionic constituents in water. Non-significant variation occurred in the EC of Filter 1 was observed O n L i n e F i r s t throughout the experiment and it remained in the range of 2 µS/cm to 2.8 µS/cm whereas in case of the Filter 2 the EC was reduced significantly from 10 µs/cm to 5 µs/cm and then remained below 4 µs/cm throughout the experiment.…”
Section: Filter Test and Water Quality Parametersmentioning
confidence: 99%
“…Before describing the findings of the present study, a concise summary of selected important results from a previous study on the same soil samples (Ratnayake et al, submitted), is briefly summarized in this paragraph. The soil is lateritic, and lateritic soils are acidic in nature 29 , acidic soils being defined as having pH less than 5.5 for most of the year 30 . Concerning this work, the sampled soils are reddish clayey rock material, with a surface area between 20 – 30 m 2 g -1 and an average soil pH of 4.4 ± 0.2 (i.e., extremely acidic 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…This makes laterite a good adsorbent. Other than that, the high porosity and the availability of anion exchange sites are beneficial for the use of laterite as an adsorbent 17,18 .…”
Section: Introductionmentioning
confidence: 99%